Electrochemical investigations of singly and doubly bridged imino[60]fullerenes - Zhou, Jinkou; Rieker, Anton; Grösser, Thomas; Skiebe, Andreas; Hirsch, Andreas (Journal of the Chemical Society, Perkin Transactions 2, 1997)
The electrochemical properties of four singly bridged (1-4) and one doubly bridged (5) N-substituted imino[60]fullerenes have been investigated with cyclic voltammetry (CV) and differential pulse voltammetry (DPV). The substituents on the imino nitrogen are methoxycarbonylmethyl (1, 2, 5), 4-(pentafluorophenoxycarbonyl)phenyl (3), and 4-(succinimidoxycarbonyl)phenyl (4). [6,6]-Bridged structures (2) with closed and [5,6]-bridged structures (1, 3, 5) with open transannular bonds were compared for the first time. Whereas C and 1-4 exhibit four successive, reversible reduction peaks in terms of an EEEE mechanism, a chemical reaction followed the cathodic reduction of 5 to 5. This effect is particularly clear in the DPV, where all subsequent reduction peaks were doubled. This can be explained by an ECEEE mechanism, in which 5 after the first E reduction undergoes a chemical transformation into one or two new species, which are further reduced in EEE processes. In the anodic oxidation of 1-5 a two-electron transfer was confirmed. In sharp contrast to all other fullerene derivatives, a quasireversible oxidation of 4 could be observed. To our knowledge, this is the first report of a quasireversible electrochemical oxidation for C mono adducts. The reduction potentials exhibit good linear relationships with the calculated LUMO energy levels. Significantly, compared to C, the reductions of the [6,6]-bridged derivative 2 as well as of the doubly [5,6]-bridged compound 5 occur at more negative potentials, whereas those of the singly [5,6]-bridged compounds 1,3,4 are found at less negative potentials.